1999
DOI: 10.1046/j.1440-1827.1999.00924.x
|View full text |Cite
|
Sign up to set email alerts
|

Ossifying fibromyxoid tumor of soft parts: Clinicopathologic, immunohistochemical and ultrastructural study of four cases

Abstract: Four cases of uncommon soft tissue tumors were investigated histopathologically. All of them consisted of fibrous and myxoid components, and mature bone showed shell-like characteristics. Histological features revealed these tumors were well circumscribed by a thick collagenous fibrous capsule and composed of uniform-sized fusiform cells with eosinophilic cytoplasm and a round or oval nucleus in the myxoid matrix. An incomplete shell of mature bone with lamellar structure was also observed at the periphery. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 12 publications
2
27
0
1
Order By: Relevance
“…Evidence exists for a schwannian or neuronal differentiation but this has not been well proven. [18][19][20] Similarly, cartilaginous or myoepithelial differentiation was proposed by Enzinger et al 2 and Kilpatrick et al, 15 respectively. From these hypotheses, Graham et al 7 suggested a ''scrambled'' phenotype for these tumors.…”
Section: Differential Diagnosesmentioning
confidence: 86%
“…Evidence exists for a schwannian or neuronal differentiation but this has not been well proven. [18][19][20] Similarly, cartilaginous or myoepithelial differentiation was proposed by Enzinger et al 2 and Kilpatrick et al, 15 respectively. From these hypotheses, Graham et al 7 suggested a ''scrambled'' phenotype for these tumors.…”
Section: Differential Diagnosesmentioning
confidence: 86%
“…In the majority of reported cases the tumor cells have shown positive immunoreaction for neural differentiation markers such as S-100 protein, neuronspecific enolase, glial fibrillary acidic protein, and Leu-7 (CD-57). 5,6,[9][10][11][12] In addition, in many cases the ultrastructural studies have demonstrated either abundant intermediate filaments or basal lamina that were partial and reduplicated, or both. [9][10][11][12] These facts mostly support neural or Schwannian differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Neural, cartilaginous, osteoblastic, myogenic, and fibroblasic origins have been postulated on the basis of immunochemistry and ultrastructural features. [1][2][3][4][5]9,11,12 The index case showed focal immunoreactivity for S-100 protein, suggesting a peripheral nerve sheath derivation.…”
Section: Discussionmentioning
confidence: 99%